Heat Shock Protein 60 Antibodies Are Associated With a Risk Factor for Cardiovascular Disease in Bedridden Elderly Patients - de Lima Filho, Jonas Bernardes; Freire, Letícia; Nahas, Eliana Aguiar Petri; Orsatti, Fábio Lera; Orsatti, Claudio Lera (Frontiers in Molecular Biosciences, 2020)
Frailty in elderly people represents multiple deficiencies in different organs and is characterized by decreased physiological reserves and greater vulnerability to stressors. Bedridden elderly with cardiovascular disease (CVD) have a worse prognosis than non-bedridden patients. Heat-shock proteins (HSPs) are molecular chaperones that under physiological conditions facilitate the transport, folding and assembly of proteins. Serum HSP 60-kDa concentrations and their antibodies are increased in response to non-physiological conditions suggesting the involvement of HSPs and their antibodies in the development of CVD. The objective of this work was to evaluate heat shock protein 60 and antibodies associated with a risk factor for cardiovascular disease in bedridden elderly patients. Clinical, analytical and cross-sectional study with 57 elderly (> 65 years). HSP60 and anti-HSP60 plasma levels were used for ELISA. Bivariate analysis using a linear regression model adjusted for risk factors used Framingham Score. Of the 57 elderly with average age 69.89 years; 39% are bedridden; 26% with pre-existing cardiovascular disease and 44% are dyslipidemic. The relationship of risk factors in the Framingham Score was positive for anti-HSP60 antibody (p = 0.042). Our data show that with each elevation of the Framingham score the anti-HSP60 antibody profile increases. These results suggest a greater immune activation that is associated with cardiovascular risk in and bedridden fragility.